ADMINISTERING THE FORUM ON CHINA AFRICA COOPERATION: EMPHASIS ON AGRICULTURAL RELATIONS - Gimba, Zainab (International Journal of Research -GRANTHAALAYAH, 2018)
The paper examines the administering of the forum on china-africa cooperation, looking at the cooperation in agricultural sector. The paper adopts the historical descriptive method of research to look into the development of the cooperation. Findings show that, chines contribution to agriculture goes beyond Africa, but covers many regions of the world and Africa benefits immensely in this cooperation. The paper concludes that china is doing its own best to see Africa grow agriculturally and expand to other areas of serving humanity. The paper recommends the involvement of all stake-holders in seeing that food security is assured in Africa.